New business ventures and the entrepreneur (Irwin/McGraw-Hill, 1999)
This text--a combination of Harvard Cases and text-- examines the entrepreneurial process from the initial idea through business operations to harvest. It provides the knowledge and skills required for students pursuing careers as entrepreneurs as well as valuable ideas for those in a more structured business setting. Most importantly, it takes a close look at the process of identifying and pursuing opportunity, which has become increasingly important in restoring the competitive position of many U.S. industries in a global marketplace.